2007
DOI: 10.1111/j.1461-9563.2007.00328.x
|View full text |Cite
|
Sign up to set email alerts
|

Feeding behaviour of the black pine beetle, Hylastes ater (Coleoptera: Scolytidae)

Abstract: 1 The feeding behaviour of Hylastes ater was investigated at 15 °C and 20 °C on a range of tree species. The role of an aggregation pheromone and the part played by olfactory cues in food selection was also investigated. 2 A distinct hierarchical preference at both 15 °C and 20 °C such that Pinus radiata > Pinus sylvestris > > Picea abies > > Rubus fruticosus = Betula pendula was shown. 3 Feeding on P. sylvestris led to the highest weight gain, closely followed by P. radiata and P. abies . Slightly elevated fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…A rise in temperature, within a favorable range, will speed up the metabolism of an insect and consequently increase its rate of development (Gullan & Cranston, 2005). Similarly, Leahy, Oliver, and Leather (2007) reported elevated feeding at increased temperatures among forestry pests which is likely due to the higher metabolic rates experienced at those temperatures as well as the effect of temperature and volatiles released from the wood, which might stimulate feeding. The results of this study concur with that of Protasov et al (2008) in Israel where adults of the gall wasp emerged from eucalypt foliage throughout the year in the greenhouse at a temperature range of 23-31 • C. However, field surveys in Israel by Mendel et al (2004), indicated that the wasp oviposits only during the warm season when the average maximum temperature has risen above 20 • C, and that wasps which inhabit galls in the winter may develop slowly or die depending on their developmental stages.…”
Section: Infestation Density Of Leptocybe Invasa In Different Agroecomentioning
confidence: 93%
“…A rise in temperature, within a favorable range, will speed up the metabolism of an insect and consequently increase its rate of development (Gullan & Cranston, 2005). Similarly, Leahy, Oliver, and Leather (2007) reported elevated feeding at increased temperatures among forestry pests which is likely due to the higher metabolic rates experienced at those temperatures as well as the effect of temperature and volatiles released from the wood, which might stimulate feeding. The results of this study concur with that of Protasov et al (2008) in Israel where adults of the gall wasp emerged from eucalypt foliage throughout the year in the greenhouse at a temperature range of 23-31 • C. However, field surveys in Israel by Mendel et al (2004), indicated that the wasp oviposits only during the warm season when the average maximum temperature has risen above 20 • C, and that wasps which inhabit galls in the winter may develop slowly or die depending on their developmental stages.…”
Section: Infestation Density Of Leptocybe Invasa In Different Agroecomentioning
confidence: 93%
“…Four branch sections, one from each tree species, were placed on a piece of filter paper (width 140 mm) in a square plastic container (height 50 mm, width 140 mm wide). The filter paper was moistened with 0.8 mL of distilled water to maintain humidity inside this arena (Raffa et al, 2002; Toivonen & Viiri, 2006; Leahy et al, 2007). One adult weevil, starved for 48 h previously, was placed inside the container, and allowed to feed on the four branches.…”
Section: Methodsmentioning
confidence: 99%
“…Root herbivores may cause chronic mortality through predisposition to fungal pathogens or above‐ground herbivores (Whitney, 1961; Hunter, 2001; Zhu et al, 2008) or the insects may girdle and kill young trees. Notable examples include weevils such as Hylastes ater (F.) (Coleoptera: Curculionidae: Scolytinae) and Hylobius abietis (L.) (Coleoptera: Curculionidae) in Europe (Eidmann, 1997; Leahy et al, 2007). In North America, an emerging concern in forest management is the Warren root collar weevil Hylobius warreni Wood (Coleoptera: Curculionidae), a native, flightless insect distributed transcontinentally throughout northern coniferous forests (Cerezke, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…unstressed) Pinus sylvestris twigs gained significantly more weight than those feeding upon damaged (i.e. stressed) twigs (Leahy, Oliver & Leather ). Similarly, the bark beetle Tomicus destruens has been found to preferentially attack nonstressed pines during its shoot feeding phase and to have increased fitness as a result (Branco et al .…”
Section: Discussionmentioning
confidence: 93%